2018
DOI: 10.1371/journal.pntd.0006288
|View full text |Cite
|
Sign up to set email alerts
|

Coverage, social mobilization and challenges of mass Zithromax administration campaign in South and South East zones of Tigray, Northern Ethiopia: A cross sectional study

Abstract: BackgroundThe antibiotic treatment of people with trachoma helps to prevent transmission the disease in a community. Currently, Zithromax is the drug recommended for mass drug administration (MDA). MDA should be carried out annually for three to five years in trachoma endemic areas. Coverage survey is essential to track progress towards program goals and to identify communities with poor coverage in order to permit timely and appropriate actions. We assessed mass Zithromax administration coverage, social mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 15 publications
(17 reference statements)
8
16
0
Order By: Relevance
“…Regarding attitudes and practices of respondents in the current study, the majority, 86.1%, of respondents agreed that taking mass drug administration is important to prevent and control trachoma and 88.1% of the respondents took mass drug administration. This result is almost comparable with the other reports from Amhara and Tigray regions, and the coverage of mass drug administration ranged from 76.8% to 93.3% [ 20 22 ]. On the other hand, 88.1% of respondents agreed that trachoma can be prevented by utilizing latrine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding attitudes and practices of respondents in the current study, the majority, 86.1%, of respondents agreed that taking mass drug administration is important to prevent and control trachoma and 88.1% of the respondents took mass drug administration. This result is almost comparable with the other reports from Amhara and Tigray regions, and the coverage of mass drug administration ranged from 76.8% to 93.3% [ 20 22 ]. On the other hand, 88.1% of respondents agreed that trachoma can be prevented by utilizing latrine.…”
Section: Discussionsupporting
confidence: 90%
“…Effective health education is the key to building the favorable attitudes on trachoma prevention and control among communities to achieve the goal of eliminating trachoma as a public health problem [ 28 , 29 ]. In Ethiopia, health extension workers and WDG leaders are giving health education to communities on personal hygiene, environmental sanitation, and mass drug administration for prevention and control of trachoma [ 22 ]. This could be the possible explanation that if mothers have received health education on trachoma, they may feel responsibility and accountability to prevent their children and families from trachoma infection.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a few women said they heard the drug can cause infertility. This is similar to studies in Ethiopia and Kenya in which women perceived azithromycin as a form of family planning [44, 45]. The origin of rumors can be complex.…”
Section: Discussionsupporting
confidence: 85%
“…Fear of side-effects, absence during the MDA campaign, drug distributor no-shows and under age status were the mentioned reason for not swallowing the drug—these are similar findings to a study conducted previously in Amhara and Tigray regional states [12, 15]. Another study conducted in Kenya also showed similar results, in which, lack of awareness, fear of side-effects, migration and grazing animals were reported as barriers to swallowing medication [16].…”
Section: Discussionsupporting
confidence: 83%